WORKING ANALYSIS OF SPACE TIME TRELLIS CODE ON WIFI MIMO(2X2) SYSTEM OFDM - Wisnu Broto; Noor Suryaningsih; Adhi Mahendra (Spektra: Jurnal Fisika dan Aplikasinya)
Wireless communication nowadays requires a system with reliable performance, efficient use of bandwidth, efficient power, and better coverage because it is in line with human needs for applications that require high and fast data rates. One of the concepts and methods to meet these needs is using an antenna technique with many transmitters and receivers or often called Multiple Input Multiple Output (MIMO), by adding a strategy at the time of delivery, namely the Space-Time Coding (STC) technique. In addition, the application of Orthogonal Frequency Division Multiplexing (OFDM) on MIMO-STC will more efficiently use bandwidth. The Space-Time Trellis Code (STTC) method is one of the diverse techniques in sending data with complex coding so that coding reinforcement is achieved and applied to the OFDM MIMO system. It is hoped that a system with reliable performance can be achieved. The simulation that is carried out presents the STTC and OFDM schemes on multi antennas (2 transmitters x 2 receivers) with a Combiner and Maximum Likelihood Sequence Estimator (MLSE) detection algorithm on the receiver. It is to get the quality of the sending signal in the performance analysis of Bit Error Rate (BER) with Signal to Noise Ratio (SNR). The simulation results are shown by modulation with M-array Phase Shift Keying (MPSK) and the number of symbols sent by giving different input parameter values. The results show that the number of carriers and the size of the Fast Fourier Transform (FFT) is large, and the modulation type with a small constellation produces a low BER and throughput at high SNR.